2015
DOI: 10.1152/ajpcell.00262.2014
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor KLF10 regulates transforming growth factor receptor II expression and TGF-β signaling in CD8+ T lymphocytes

Abstract: KLF10 has recently elicited significant attention as a transcriptional regulator of transforming growth factor-β1 (TGF-β1) signaling in CD4+ T cells. In the current study, we demonstrate a novel role for KLF10 in the regulation of TGF-β receptor II (TGF-βRII) expression with functional relevance in antiviral immune response. Specifically, we show that KLF10-deficient mice have an increased number of effector/memory CD8+ T cells, display higher levels of the T helper type 1 cell-associated transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…For example, it would be of interest to assess the relative ratio of CD8 ϩ Tregs versus CD8 ϩ T cell effectors in response to viral pathogens. The expansion of KLF10 Ϫ/Ϫ CD8 ϩ T cells observed by Papadakis et al (6) aligns well with the known role of TGF-␤ on CD8 ϩ T cell homeostasis-abrogation of TGF-␤ signaling leads to marked T cell expansion including memory CD8 ϩ T cells (4). However, whether KLF10 is the primary downstream mediator of this TGF-␤1-driven CD8 T cell expansion remains to be determined.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…For example, it would be of interest to assess the relative ratio of CD8 ϩ Tregs versus CD8 ϩ T cell effectors in response to viral pathogens. The expansion of KLF10 Ϫ/Ϫ CD8 ϩ T cells observed by Papadakis et al (6) aligns well with the known role of TGF-␤ on CD8 ϩ T cell homeostasis-abrogation of TGF-␤ signaling leads to marked T cell expansion including memory CD8 ϩ T cells (4). However, whether KLF10 is the primary downstream mediator of this TGF-␤1-driven CD8 T cell expansion remains to be determined.…”
supporting
confidence: 76%
“…Previous studies indicate that TGF-␤ signaling induces CD8 ϩ T cell differentiation by increasing IL-7R␣ expression as well as emigration of CD8 ϩ T cell effectors from the spleen to the organs such as the gut by regulating integrin ␣ 4 ␤ 7 expression. While Papadakis et al (6). found no differences in the total number of peripheral CD8 ϩ T cells in KLF10 Ϫ/Ϫ mice compared with wild-type (WT) mice, the ratio of CD8 ϩ T cell effectors to naïve T cells was markedly increased in KLF10 Ϫ/Ϫ mice.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, these considerations led us in this study to search for cellular and molecular mechanisms that acting downstream of TGF-␤ signaling may contribute to colitis. In this regard, recent studies have identified a role for TGF-␤-inducible early gene 1 or KLF10, which belongs to the family of Sp1/Krüppel-like zinc finger transcription factors (31), in T lymphocytes and innate immune cells (5,23,34,39).…”
Section: And Cd4mentioning
confidence: 99%